The manuscript poems of A.E. Housman : eight hundred lines of hitherto uncollected verse from the author's notebooks - Housman, A. E. (Alfred Edward), 1859-1936 (University of Minnesota Press, 1955)
Poetry lovers everywhere, and devotees of A.E. Housman in particular, will recognize a major literary event in the publication of this volume, for it makes available for the first time some 800 lines of hitherto unpublished poetry by the well-loved autho.